Menjembatani Masa Depan Pendidikan Indonesia: Memanfaatkan Teknologi Untuk Mengatasi Tantangan Lokal dan Global - Nidda Adzkya Nurfitria; Naila Melany (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
Quality education is the key to advancing a nation, but there are still several challenges that must be faced to achieve it. This article aims to examine how technology can be applied to overcome educational problems both locally and internationally. Through the literature review method, this research evaluates literature reviews related to technology that has been successfully applied to solve educational problems. The future of Indonesian education is believed to be colored by the increasingly massive use of technology. Technology allows students and teachers to easily access information and learning resources from around the world. This broadens horizons and enriches the learning process as well as presenting new opportunities and challenges in the teaching and learning process. Challenges faced in implementing educational technology include gaps in internet access, lack of digital literacy and cultural barriers.